CEMETERY: MORE HUMAN, INTELLIGENT, AND SUSTAINABLE - Agostini, Armando L. Carvalho; da Costa, Eduardo Moreira; Manfroi, Carlo; dos Santos, Neri; Pereira, Ricardo (Seven Editora, 2026)
This article discusses the main problems of traditional cemeteries in urban centers, including the lack of space due to population growth, environmental contamination from the use of toxic products in burials, public health issues arising from poor management and maintenance, and cultural and religious issues that make the grieving experience more challenging. The goal is to propose a new cemetery model integrated into urban planning that minimizes environmental impacts and offers a more humane experience for families and visitors, contributing to the sustainable development of cities. Additionally, this work highlights the importance of interdisciplinary research and partnerships between government, the private sector, and academia to develop this new cemetery paradigm. The method used was an integrative review on the subject. The article first addresses the current problems of traditional cemeteries; then, it introduces concepts of smart and sustainable cities that can be applied to cemeteries; and finally, it suggests the implementation of a new model for cemeteries, including the addition of green spaces, efficient use of water resources and solar energy, artificial intelligence-based monitoring systems, as well as virtual memorials and other innovations. Certainly, this innovative model has the potential to create a more humane and sustainable environment for urban cemeteries by integrating smart technologies and meeting the cultural and emotional needs of communities.